Generating Mechanism of Online Public Opinion Heat in Public Emergencies from the Perspective of Information Ecology: Fuzzy Set Qualitative Comparative Analysis Based on 50 Cases - YOU Ge, LI Jielin, ZHANG Fangshun (Nongye tushu qingbao xuebao)
[Purpose/Significance] Public emergencies frequently trigger online public opinion, exacerbating public panic and threatening social stability. The intrinsic linkage between public emergencies and online discourse amplifies the dissemination of public emotions, attitudes, and perspectives across online platforms, creating a feedback loop that influences event dynamics. Investigating the generation mechanism of public opinion on hot topics in such contexts provides critical theoretical foundations for mitigating cyber discourse risks, while enhancing the accuracy and efficiency of governmental mangement over online public opinion. [Method/Process] From an information ecology perspective, this study employs fuzzy-set qualitative comparative analysis to examine the online public opinion heat of 50 public emergencies between 2020 and 2022. We analyze eight conditional variables across four dimensions - information, information person, information technology, and information environment - including peak propagation speed, peak event popularity, netizen attention, opinion leaders' communication power, important media participation, central media coverage, the proportion of the overall public opinion field, and event duration. Single-factor necessity detection and configuration analysis were performed, and robustness was tested by adjusting calibration points and consistency thresholds. Finally, based on empirical findings, we interpreted case studies and proposed a mechanism for the generation of online public opinion heat in public emergencies. [Results/Conclusions] The results reveal that information and information people are the primary drivers and key causes of hot public opinion. Although information environment and information technology are not necessary conditions, they still contribute to the process. In public emergencies, multiple factors jointly influence online public opinion, and no single factor alone determines its intensity. Rather, the complementarity of multiple factors can, to some extent, substitute for seemingly necessary conditions. The key findings reveal that the event's peak plays a dominant role in driving high online public opinion intensity, and directly triggers its rapid outbreak, while the absence of major media participation and short event duration - core conditions for non-hot events - significantly reduce public engagement due to limited coverage and transient attention. Additionally, opinion leaders' communication power exhibits a strong positive correlation with public opinion on hot topics, as their amplified expressions attract more attention from netizens and further amplify the momentum of the discourse. These findings will provide valuable insights for effectively managing and controlling online public opinion during emergencies. Future research should examine the impact of emotional shifts, such as positive, negative, and neutral emotions, on the virality of online public opinion during emergencies, while also exploring the underlying mechanisms of such emotional shifts. Additionally, future studies should differentiate between policy stages in emergency development and examine how policy interventions shape the dynamics of public opinion. Finally, network analysis techniques (e.g., forwarding relationship networks, key evolutionary network structures) should be employed to uncover the mechanisms that drive public opinion heat in emergency-related discourse.